From farm to industry: An overview of tomatoes, lycopene's health benefits, and the sustainable valorization of by-products (Research, Society and Development, 2025)
This study aims to review the current knowledge on tomatoes and carotenoids, particularly lycopene, highlighting their health benefits and the sustainable utilization of by-products from the tomato processing industry. Belonging to the Solanaceae family, the tomato (Solanum lycopersicum L.) is one of the most consumed vegetables worldwide, appreciated both fresh and in processed products. The tomato industry generates a large volume of waste, and improper management can cause environmental issues, besides leading to the loss of valuable bioactive compounds such as lycopene. Lycopene possesses high antioxidant capacity, and its consumption has been associated with a reduced risk of certain types of cancer and cardiovascular diseases. Innovative and sustainable extraction methods, including the use of green solvents and technologies such as supercritical fluid, ultrasound-assisted, and other emerging techniques, are being explored to optimize the valorization of these by-products, contributing to the circular economy and sustainability. Further research is needed to overcome current challenges and promote solutions for reducing environmental impacts, achieving efficient and sustainable extraction, lowering costs, and improving the scalability of extraction technologies to obtain high-value products for various applications.